Analysis of Internal Control Information System Product Conversion Cycle Management: Analisis Pengendalian Internal Sistem Informasi Manajemen Siklus Konversi Produk - Maghfiro, Putri Lailatul; Setiyono, Wisnu Panggah (Indonesian Journal of Innovation Studies, 2022)
Suppliy is one of thei iimportant assiet hiad biy compiany. Becausie suppliy repriesent assiet of hience muist be done interinal contriol whiich is good to takiing carie of thie suppliy from ugliy thiings is whiich is possibile happiened the. Systeim of interinal contriol of sttock to contriol anid manaige thei stiock. Espiecial tariget friom operaition to the suppliy is protiect the suppliy and reporit it precisiely in fiinancial statiement. Methiod usedi by is apprioach methodi qualitatiive that iis, descriiptive analysiis. From resiearch resiult at Konter Phoenix Jaya Cabang Krian repriesent a periipatetic compiany is area of fruiit distriibutor iimport, or more knowledgeabile as fruiiterer iimport the griocery and at retaiil. Sysitem evaluatiion, iinternal contriol to the suppliy have effectiive, whiere exiistence of dutiy diissociation of betiween functiions of relaited to revienue and expendiiture goods. Moniitoring to merchaniidise stoick is allso condiucted routiinely eaich;everry oine montth oncce by warehiouse sharies through the stock actiivity hospitaliize tthe. Systiem off iinventory contriol of merchandiise at Konter Phoenix Jaya branch Krian have waliked betiter.